Upaya Meningkatkan Hasil Belajar Peserta Didik dalam Mata Pelajaran Simulasi dan Komunikasi Digital Menggunakan Model Problem Based Learning Berbantuan Media Pembelajaran Si-Bajakah: Efforts to Improve Student Learning Outcomes in Digital Simulation and Communication Subjects Using Problem Based Learning Models Assisted by Si-Bajakah Learning Media - Ainah , Siti Nor; Hendri, Hendri; Permadi, Ade Salahudin (Martyvel: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to: (1) Decrypt the learning activities of students after using si-bajakah learning media. (2) Improving student learning outcomes in Simulation learning and digital communication using the Problem Based Learning model assisted by Si-Bajakah learning media. The method and type of research used in this study is Classroom Action Research (PTK). The subjects in this study were class X students of SMK Negeri 3 Palangkaraya, totaling 9 people. The data collection techniques in this study are Observation and Test. Meanwhile, data analysis techniques use qualitative analysis and quantitative analysis. The results of this study show that: (1) The learning activities of students during the application of the Problem Based Learning model assisted by Si-Bajakah learning media in the subject of Simulation and Digital Communication at SMK Negeri 3 Palangkaraya are good. This can be seen in the acquisition of the average score of the first cycle of 2.90. Meanwhile, the average score of cycle II is 3. (2) There is an increase in the learning outcomes of Simulation and Digital Communication in the application of the Problem Based Learning model assisted by Si-Bajakah learning media in the Simulation and Digital Communication subjects at SMK Negeri 3 Palangkaraya where in the initial data (pre-test) an average score of 60.22 with a classical completion of 33.33% was obtained. In Cycle I obtained an average value of 72.22 with a classical completion of 44.44%. Furthermore, in Cycle II, students obtained an average score of 84.44 with a classical completion of 100%.